Impact-resistant electromagnetic shielding composite film with strain rate effect and preparation method and application thereof

CN122976149APending Publication Date: 2026-10-27SUZHOU INST OF NANO TECH & NANO BIONICS CHINESE ACEDEMY OF SCI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510525354.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]常规电磁屏蔽材料大多数为金属或塑料制品/屏蔽填料的复合材料,但这种常规材料体积大、重量大,形状固定且不易安装

Benefits of technology

[0014]与现有技术相比,本发明的有益效果包括:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122976149A_ABST
    Figure CN122976149A_ABST
Patent Text Reader

Abstract

The application discloses an impact-resistant electromagnetic shielding composite film with a strain rate effect and a preparation method and application thereof. The preparation method comprises the following steps: reacting boric acid with hydroxyl-terminated dimethyl silicone oil to prepare a shear thickening glue; mixing a silicone rubber prepolymer with a curing agent to obtain a crosslinking precursor; mixing the shear thickening glue with the crosslinking precursor and extruding to obtain an uncrosslinked shear thickening glue film; and hot-pressing after arranging the uncrosslinked shear thickening glue film on both sides of a conductive structure layer to realize chemical network crosslinking of the uncrosslinked shear thickening glue film and simultaneously realize compounding with the conductive structure layer, so as to prepare the impact-resistant electromagnetic shielding composite film with the strain rate effect. The impact-resistant electromagnetic shielding composite film prepared by the application is small in volume and light in weight, can realize the intelligent impact resistance performance of "soft in normal state and hardened in impact state" by virtue of the shear hardening glue component, has a typical strain rate effect, and can realize electromagnetic shielding in a wide wave band of 300M-40GHZ.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an electromagnetic shielding film, specifically to an impact-resistant electromagnetic shielding composite film with strain rate effect, its preparation method, and its application, belonging to the field of materials science and technology. Background Technology

[0002] With the rapid development of electromagnetic technology, electromagnetic-related technologies have been widely applied in the fields of communication, energy, medicine, and transportation, driving the rapid development of these technologies. However, the widespread application of electromagnetic technology has also filled the environment with complex electromagnetic spectrum interference. This interference can cause damage to sensitive electronic equipment due to overload, data loss during data transmission, and system malfunction in weaponry. When electromagnetic shielding materials are used in special scenarios such as automotive protection, weapon protection, and space protection, they are required not only to possess excellent electromagnetic shielding performance but also to withstand impacts and fragmentation. Existing material systems still fall short of meeting these application requirements.

[0003] Conventional electromagnetic shielding materials are mostly composite materials of metal or plastic products / shielding fillers. However, these conventional materials are bulky, heavy, have fixed shapes, and are difficult to install. Chinese patent CN106170385A reports a semi-finished composite material consisting of two layers of plastic sheets covering a middle shielding layer. This overcomes the problem of excessive weight of metal shielding materials to some extent, but it still suffers from bulkiness and difficulty in installation, and the material system lacks impact resistance. Furthermore, metal or plastic composite shielding materials are difficult to flexibly match the electromagnetic shielding requirements of irregularly shaped components in practical applications, usually requiring custom-made molds, resulting in high manufacturing costs and poor economic efficiency. Moreover, ordinary shear-hardening adhesives exhibit leakage and cannot achieve effective long-term stable bonding with other materials. Summary of the Invention

[0004] The main objective of this invention is to provide an impact-resistant electromagnetic shielding composite film with strain rate effect and its preparation method, so as to overcome the shortcomings of the prior art.

[0005] Another object of the present invention is to provide the application of the aforementioned shock-resistant electromagnetic shielding composite film with strain rate effect.

[0006] To achieve the aforementioned objectives, the technical solution adopted by this invention includes:

[0007] This invention provides a method for preparing an impact-resistant electromagnetic shielding composite film with strain rate effect, comprising:

[0008] Boric acid was reacted with hydroxyl-terminated dimethyl silicone oil to prepare a shear-thickening adhesive.

[0009] The silicone rubber prepolymer is mixed with a curing agent to obtain a crosslinking precursor;

[0010] The shear thickener is mixed with a crosslinking precursor and extruded to obtain an uncrosslinked shear thickener film.

[0011] Uncrosslinked shear-thickening films are respectively placed on the two opposite surfaces of the conductive structural layer, and then hot-pressed to achieve chemical network crosslinking of the uncrosslinked shear-thickening films. At the same time, they are composited with the conductive structural layer to obtain an impact-resistant electromagnetic shielding composite film with strain rate effect.

[0012] This invention also provides an impact-resistant electromagnetic shielding composite film with strain rate effect prepared by the aforementioned preparation method, which includes a conductive structural layer and cross-linked shear thickening films respectively laminated on the back-to-back surfaces of the conductive structural layer.

[0013] This invention also provides applications of the strain rate-effect-resistant electromagnetic shielding composite film in fields such as electronic component protection, aircraft protection, automotive collision avoidance, or aerospace environment equipment particle collision avoidance.

[0014] Compared with the prior art, the beneficial effects of the present invention include:

[0015] 1) The impact-resistant electromagnetic shielding composite film material prepared by this invention is small in size and light in weight. With the shear-hardening adhesive component, it can achieve intelligent impact resistance performance of "soft under normal conditions and hardened under impact conditions". It can achieve electromagnetic shielding performance of more than 40dB at the millimeter scale and exhibits strain rate effect. When it is used for the protection of electronic components or aircraft, it can meet the development needs of lightweight.

[0016] 2) The impact-resistant electromagnetic shielding composite film material prepared by this invention has lightweight and flexible characteristics, can be folded and processed in a flexible manner, and is easy to match the installation requirements of irregular parts for electromagnetic shielding materials. Compared with traditional mold customization, the impact-resistant electromagnetic shielding film material is more economical.

[0017] 3) The cured shear-hardening adhesive forms an effective interfacial bond with the carbon nanotube film, which can maintain the stability of physical morphology and performance for a long time, overcome the disadvantage of easy leakage of this type of material, and ensure the reliability of the material's impact resistance. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 This is a schematic diagram illustrating the preparation of an impact-resistant electromagnetic shielding composite film with strain rate effect in a typical embodiment of the present invention.

[0020] Figure 2A , Figure 2B These are, respectively, a microscopic morphology image and a magnified image of a portion of the contact surface of the impact-resistant electromagnetic shielding composite film with strain rate effect prepared in Example 1 of the present invention.

[0021] Figure 3 This is a flexible display diagram of the impact-resistant electromagnetic shielding composite film with strain rate effect prepared in Embodiment 1 of the present invention.

[0022] Figure 4 This is a test diagram of the areal density of the impact-resistant electromagnetic shielding composite film with strain rate effect prepared in Example 1 of the present invention.

[0023] Figure 5 This is a schematic diagram of the electromagnetic shielding effectiveness of the shock-resistant electromagnetic shielding composite films with strain rate effect of different thicknesses prepared in Example 1 of the present invention, and the composite films obtained in Comparative Examples 1-2 in the range of 0.03-40GHz.

[0024] Figure 6 The impact-resistant electromagnetic shielding composite film C-STG-0.75 with strain rate effect prepared in Example 1 of this invention, and the composite films obtained in Comparative Examples 1-2, exhibit a strain rate effect at 600 s. -1 700s -1 800s -1 Stress-strain curves under strain rate. Detailed Implementation

[0025] Carbon nanotube films (CNFs) are only 10-20 μm thick, and their internal structure is formed by densely packed carbon nanotubes. This excellent conductive pathway gives the material superior electromagnetic shielding performance. Compared to common metal shielding materials, carbon nanotube films are lightweight and flexible, making them an excellent choice for flexible shielding materials. Shear-hardening adhesives are polydimethylsiloxane polymers with a dynamically cross-linked internal structure, exhibiting a soft material under normal conditions. When subjected to external impact, based on their shear hardening effect, they can undergo a "soft-to-hard" transition without other excitation conditions, exhibiting good impact resistance.

[0026] In view of the shortcomings of the existing technology, the inventors of this invention have conducted extensive and in-depth research and prepared a lightweight, flexible and easy-to-install impact-resistant electromagnetic shielding composite film. This invention utilizes carbon nanotube films prepared by chemical vapor deposition and modified shear thickening adhesive for hot-pressing composite to prepare a lightweight, flexible impact-resistant electromagnetic shielding composite film with a "sandwich structure". This material has a typical strain rate effect and can achieve electromagnetic shielding in a wide wavelength range.

[0027] The following terms require explanation:

[0028] Strain rate effect: The phenomenon that the mechanical properties of a material change with the strain rate when it is subjected to external force.

[0029] The following will provide a further explanation of the technical solution, its implementation process, and its principles.

[0030] As one aspect of the technical solution of this invention, a method for preparing an impact-resistant electromagnetic shielding composite film with strain rate effect includes:

[0031] Boric acid was reacted with hydroxyl-terminated dimethyl silicone oil to prepare a shear-thickening adhesive.

[0032] The silicone rubber prepolymer is mixed with a curing agent to obtain a crosslinking precursor;

[0033] The shear thickener is mixed with a crosslinking precursor and extruded to obtain an uncrosslinked shear thickener film.

[0034] Uncrosslinked shear-thickening films are respectively placed on the two opposite surfaces of the conductive structural layer, and then hot-pressed to achieve chemical network crosslinking of the uncrosslinked shear-thickening films. At the same time, they are composited with the conductive structural layer to obtain an impact-resistant electromagnetic shielding composite film with strain rate effect.

[0035] In some embodiments, the mass ratio of boric acid to hydroxyl-terminated dimethyl silicone oil is 1:15 to 1:8.

[0036] In some embodiments, the reaction temperature is 160–200°C and the reaction time is 2–5 hours.

[0037] In some embodiments, the silicone rubber prepolymer and the curing agent are selected from components A and B of Slyard 184 silicone rubber, respectively. Component A is the silicone rubber prepolymer and component B is the curing agent. The two must be mixed to achieve cross-linking and curing.

[0038] Furthermore, the mass ratio of component A to component B is 10:1 to 6:1.

[0039] In some embodiments, the mass ratio of the shear thickener to the crosslinking precursor is 8:1 to 4:1. If the shear thickener component is too high, the composite material will have an unstable morphology; if the shear thickener component is too low, it will be difficult to guarantee the material's impact resistance.

[0040] In some embodiments, the preparation method includes: mixing the shear thickener with a crosslinking precursor to form a mixture, extruding the mixture using a twin-screw extruder, and then placing it in a mold to obtain an uncrosslinked shear thickener film.

[0041] In some embodiments, the thickness of the uncrosslinked shear-thickening film is 0.5 to 1.5 mm.

[0042] In some embodiments, the conductive structural layer may be a carbon nanotube film, or at least one of other conductive metal coatings.

[0043] Furthermore, the thickness of the conductive structure layer is 20–50 μm.

[0044] In some embodiments, the hot-pressing temperature is 70–90°C, and the hot-pressing time is 10–30 minutes. During the hot-pressing process, the shear-hardening adhesive on both sides of the material solidifies, maintaining long-term physical stability and overcoming the leakage tendency of such materials. This allows for effective interfacial bonding with conductive structural layers such as carbon nanotube films, while simultaneously suppressing leakage of the shear-hardening adhesive. The physical morphology and properties of the impact-resistant electromagnetic shielding film material remain stable over a long period, ensuring the reliability of the material's impact resistance.

[0045] This invention utilizes carbon nanotube films prepared by chemical vapor deposition to hot-press composite with shear thickening adhesive to prepare a lightweight, flexible, impact-resistant electromagnetic shielding composite film with a "sandwich structure". This material exhibits a typical strain rate effect and can achieve electromagnetic shielding over a wide wavelength range.

[0046] As another aspect of the technical solution of the present invention, it relates to an impact-resistant electromagnetic shielding composite film with strain rate effect prepared by the aforementioned preparation method, which includes a conductive structural layer and cross-linked shear thickening adhesive film respectively laminated on the two back-to-back surfaces of the conductive structural layer.

[0047] Furthermore, the thickness of the shock-resistant electromagnetic shielding composite film with strain rate effect is 1-3 mm.

[0048] Furthermore, the shock-resistant electromagnetic shielding composite film with strain rate effect has a strain rate effect.

[0049] Furthermore, the shock-resistant electromagnetic shielding composite film with strain rate effect exhibits electromagnetic shielding performance exceeding 40 dB at the millimeter scale. The shock-resistant electromagnetic shielding composite film of this invention achieves intelligent shock resistance by virtue of its shear-hardening adhesive component, which is "soft under normal conditions and hardens under impact"; the conductive structural layer components, such as carbon nanotube films, achieve excellent electromagnetic shielding performance over a wide wavelength range.

[0050] Furthermore, the impact-resistant electromagnetic shielding composite film material prepared by this invention has lightweight and flexible properties, and can be flexibly folded and post-processed according to the usage requirements of various irregular parts. It is easy to match the installation requirements of irregular parts for electromagnetic shielding materials. Compared with traditional mold customization, the impact-resistant electromagnetic shielding composite film material is more economical.

[0051] As another aspect of the technical solution of the present invention, the application of the shock-resistant electromagnetic shielding composite film with strain rate effect is involved.

[0052] Specifically, the impact-resistant electromagnetic shielding composite film material prepared by this invention is small in size and light in weight. It can achieve electromagnetic shielding performance of more than 40dB at the millimeter scale and exhibits strain rate effect. When used for the protection of electronic components or aircraft, it can meet the development needs of lightweighting.

[0053] Furthermore, the impact-resistant electromagnetic shielding composite thin film material prepared by this invention is of great significance for automotive collision avoidance and particle collision avoidance for aerospace environmental equipment.

[0054] The technical solution of the present invention is further described below with reference to several embodiments and accompanying drawings, but the present invention is not limited to the scope of the embodiments described herein. The reagents and raw materials used in the following embodiments are all commercially available, and the test methods not specifically specified are generally performed under conventional conditions or according to the conditions recommended by the respective manufacturers.

[0055] Example 1

[0056] Please see Figure 1As shown, the specific steps of an impact-resistant electromagnetic shielding composite film with strain rate effect include:

[0057] (1) Boric acid and terminal hydroxyl dimethyl silicone oil were mixed evenly at a mass ratio of 1:15 and reacted at 185°C for 3 hours. The mixture was then cooled to room temperature to obtain a shear-thickened adhesive. The crosslinking precursor was obtained by mixing components A and B of Slyard 184 silicone rubber at a mass ratio of 10:1.

[0058] (2) STG and crosslinking precursor are mixed at a mass ratio of 4:1. The mixture is then uniformly mixed using a twin-screw extruder and extruded at 30 rpm. The mixture is then placed in a mold to obtain an uncrosslinked shear-thickening gel (UC-STG).

[0059] (3) A series of UC-STG films with thicknesses of 0.5 mm, 0.75 mm, 1 mm, and 1.5 mm were hot-pressed with CNF at 80 °C for 30 min to form composites. During the hot-pressing process, UC-STG achieved chemical network cross-linking, thus bonding with CNF. The resulting composite material had CNF as the middle interlayer and crosslinked shear-thickening gel (C-STG) film layers on the top and bottom. The resulting series of flexible, impact-resistant electromagnetic shielding composite films were designated as C-STG-0.5, C-STG-0.75, C-STG-1, and C-STG-1.5, respectively.

[0060] The microstructure of the impact-resistant electromagnetic shielding composite film (C-STG-0.75) prepared in this embodiment is as follows: Figure 2A As shown in the enlarged view of the contact surface between CNF and C-STG, see below. Figure 2B As shown.

[0061] Figure 3 This demonstrates the flexibility of the composite thin film material (C-STG-0.75), which can be folded into various shapes at will.

[0062] Figure 4 The areal density of the composite thin film material (C-STG-0.75) is only 0.97 kg / m³. 2 .

[0063] Figure 5 This is a schematic diagram showing the electromagnetic shielding effectiveness of a series of shock-resistant electromagnetic shielding composite films with strain rate effect of different thicknesses prepared in this embodiment in the range of 0.03-40GHz.

[0064] Figure 6The strain rate-effect-resistant electromagnetic shielding composite film (C-STG-0.75) prepared in this embodiment exhibits an impact resistance of 600 s. -1 700s -1 800s -1 Stress-strain curves under strain rate.

[0065] Example 2

[0066] (1) Boric acid and terminal hydroxyl dimethyl silicone oil were mixed evenly at a mass ratio of 1:10 and reacted at 200°C for 3 hours. The mixture was then cooled to room temperature to obtain a shear-thickened adhesive. Slyard 184 silicone rubber components A and B were mixed at a mass ratio of 10:1 to obtain a crosslinking precursor.

[0067] (2) STG and crosslinking precursor are mixed at a mass ratio of 4:1. The mixture is then uniformly mixed using a twin-screw extruder and extruded at 40 rpm. The mixture is then placed in a mold to obtain an uncrosslinked shear-thickening gel (UC-STG).

[0068] (3) A series of UC-STG with thicknesses of 0.5 mm, 0.75 mm, 1 mm, and 1.5 mm were hot-pressed with CNF at 70 °C for 10 min to form composites. During the hot-pressing process, UC-STG achieved chemical network cross-linking and bonding with CNF. The resulting composite material has CNF as the middle interlayer and crosslinked shear-thickening gel (C-STG) film layers on the top and bottom, ultimately yielding a series of flexible, impact-resistant electromagnetic shielding composite films.

[0069] Example 3

[0070] (1) Boric acid and terminal hydroxyl dimethyl silicone oil were mixed evenly at a mass ratio of 1:15 and reacted at 200°C for 2 hours. The mixture was then cooled to room temperature to obtain a shear-thickened adhesive. Slyard 184 silicone rubber components A and B were mixed at a ratio of 8:1 to obtain a crosslinking precursor.

[0071] (2) STG and crosslinking precursor are mixed at a mass ratio of 8:1. The mixture is then uniformly mixed using a twin-screw extruder and extruded at 50 rpm. The mixture is then placed in a mold to obtain an uncrosslinked shear-thickening gel (UC-STG).

[0072] (3) A series of UC-STG layers with thicknesses of 0.5 mm, 0.75 mm, 1 mm, and 1.5 mm were hot-pressed with CNF at 90 °C for 20 min to form composites. During the hot-pressing process, UC-STG underwent chemical network cross-linking, achieving bonding with CNF. The resulting composite material had CNF as the middle interlayer and crosslinked shear-thickening gel (C-STG) layers on the top and bottom. The final product was a series of flexible, impact-resistant electromagnetic shielding composite films.

[0073] Example 4

[0074] (1) Boric acid and terminal hydroxyl dimethyl silicone oil were mixed evenly at a mass ratio of 1:10 and reacted at 160°C for 5 hours. The mixture was then cooled to room temperature to obtain a shear-thickened adhesive. Slyard 184 silicone rubber components A and B were mixed at a mass ratio of 6:1 to obtain a crosslinking precursor.

[0075] (2) Mix STG and crosslinking precursor at a mass ratio of 6:1, mix evenly using a twin-screw extruder, extrude at 60 rpm and place in a mold to obtain uncrosslinked shear-thickening gel (UC-STG).

[0076] (3) A series of UC-STG with thicknesses of 0.5 mm, 0.75 mm, 1 mm, and 1.5 mm were hot-pressed with CNF at 80 °C for 30 min to form composites. During the hot-pressing process, UC-STG achieved chemical network cross-linking and bonding with CNF. The resulting composite material has CNF as the middle interlayer and crosslinked shear-thickening gel (C-STG) film layers on the top and bottom, ultimately yielding a series of flexible, impact-resistant electromagnetic shielding composite films.

[0077] Comparative Example 1

[0078] The difference between this comparative example and Example 1 is that in step (2), the mass ratio of STG to the crosslinking precursor is 10:1. The changes in electromagnetic shielding performance and impact resistance of the obtained composite film are shown in the figures below. Figure 5 and Figure 6 The electromagnetic shielding effectiveness remained largely unchanged, but the impact resistance decreased. This was because the content of the crosslinking precursor was too low, making it impossible to form a complete crosslinking network to support the rapid dissipation of energy in the composite material.

[0079] Comparative Example 2

[0080] The difference between this comparative example and Example 1 is that in step (2), the mass ratio of STG to the crosslinking precursor is 3:1. The changes in electromagnetic shielding performance and impact resistance of the obtained composite film are shown in the figures below. Figure 5 and Figure 6 The electromagnetic shielding effectiveness remained largely unchanged, but the impact resistance decreased. This was due to the low STG content, which reduced the overall shear hardening properties of the composite material, resulting in a weakened energy dissipation capacity.

[0081] In addition, the inventors of this case also conducted experiments with other raw materials and conditions listed in this specification, referring to the aforementioned embodiments, and obtained similar results.

[0082] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A method for preparing an impact-resistant electromagnetic shielding composite film with strain rate effect, characterized in that, include: Boric acid was reacted with hydroxyl-terminated dimethyl silicone oil to prepare a shear-thickening adhesive. The silicone rubber prepolymer is mixed with a curing agent to obtain a crosslinking precursor; The shear thickener is mixed with a crosslinking precursor and extruded to obtain an uncrosslinked shear thickener film. Uncrosslinked shear-thickening films are respectively placed on the two opposite surfaces of the conductive structural layer, and then hot-pressed to achieve chemical network crosslinking of the uncrosslinked shear-thickening films. At the same time, they are composited with the conductive structural layer to obtain an impact-resistant electromagnetic shielding composite film with strain rate effect.

2. The preparation method according to claim 1, characterized in that: The mass ratio of boric acid to terminal hydroxyl dimethyl silicone oil is 1:15 to 1:8; and / or the reaction temperature is 160 to 200°C, and the reaction time is 2 to 5 hours.

3. The preparation method according to claim 1, characterized in that: The silicone rubber prepolymer and curing agent are selected from components A and B of Slyard 184 silicone rubber, respectively; preferably, the mass ratio of component A to component B is 10:1 to 6:

1.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the shear thickener to the crosslinking precursor is 8:1 to 4:1; and / or, the preparation method includes: mixing the shear thickener with the crosslinking precursor to form a mixture, extruding the mixture using a twin-screw extruder at 30 rpm to 60 rpm, and then placing it in a mold to obtain an uncrosslinked shear thickener film.

5. The preparation method according to claim 1, characterized in that: The thickness of the uncrosslinked shear-thickening film is 0.5–1.5 mm.

6. The preparation method according to claim 1, characterized in that: The conductive structural layer includes at least one of carbon nanotube thin film and conductive metal coating; and / or, the thickness of the conductive structural layer is 20 to 50 μm.

7. The preparation method according to claim 1, characterized in that: The hot pressing temperature is 70–90 μm, and the hot pressing time is 10–30 min.

8. An impact-resistant electromagnetic shielding composite film with strain rate effect prepared by any one of claims 1-7, comprising a conductive structural layer and cross-linked shear-thickening adhesive films respectively bonded to opposite sides of the conductive structural layer.

9. The shock-resistant electromagnetic shielding composite film with strain rate effect according to claim 8, characterized in that: The thickness of the shock-resistant electromagnetic shielding composite film with strain rate effect is 1-3 mm; And / or, the shock-resistant electromagnetic shielding composite film with strain rate effect has a strain rate effect; And / or, the shock-resistant electromagnetic shielding composite film with strain rate effect has an electromagnetic shielding performance of more than 40 dB at the millimeter size.

10. The application of the shock-resistant electromagnetic shielding composite film with strain rate effect as described in claim 9 in the fields of electronic component protection, aircraft protection, automotive anti-collision, or aerospace environment equipment anti-particle collision.

Citation Information

Patent Citations

  • Semi-finished product made from composite material, comprising a flexible electromagnetic shielding film

    CN106170385A